Women’s Head Covering in Acehnese Tafsīr: Genealogical and Socio-Historical Readings of Two Vernacular Exegeses - Lestari, Lenni; Nur Ichwan, Moch.; Rafiq, Ahmad (UIN Sunan Kalijaga Yogyakarta, 2026)
This article examines how women’s head covering is interpreted in Acehnese exegetical works across two centuries by comparing Tarjumān al-Mustafīd of ‘Abd al-Ra’ūf al-Fansūrī al-Singkilī (d. 1693) and Al-Qur’an al-Karim dan Terjemahan Bebas Bersajak dalam Bahasa Aceh by Tengku Mahjiddin Jusuf (d. 1994). Using a genealogical approach and social-historical reading, it traces the interpretive transmission and local adaptation of key Qur’anic terms related to female modesty—especially khimār/khumur, jalābīb, and juyūb—within Aceh’s shifting socio-political contexts. The analysis shows that Acehnese meanings of head covering are not fixed outcomes of the Qur’anic lexicon alone, but emerge through selective appropriation of earlier Sunni authorities and vernacularization into local dress-terms (e.g., telekung/sileukom and ija tob ulé). Social-historical comparison further indicates that al-Singkilī’s reading helped form an early interpretive horizon of female modesty in the period of royal governance, whereas Jusuf’s interpretation functions as a reinforcing discourse in a later setting no longer shaped by sultanate structures. Overall, the study clarifies how vernacular tafsīr operates as a mediating space where Qur’anic language, inherited exegetical authority, and local social practice continually reshape one another.